![](https://cv01.studmed.ru/view/d4240582969/bg15a.png)
The chain rule can be used to explain what happens to the m when differentiating e
mx
. The
outer function is the exponential, which differentiates to itself, and the inner function is mx,
which differentiates to m. Hence, by the chain rule,
if y = e
mx
then = e
mx
× m = me
mx
Similarly, noting that the natural logarithm function differentiates to the reciprocal function,
if y = ln mx then =×m =
The chain, product and quotient rules can be used to differentiate more complicated func-
tions involving e
x
and ln x.
1
x
1
mx
dy
dx
dy
dx
4.8 • The derivative of the exponential and natural logarithm functions
335
Example
Differentiate
(a) y = x
3
e
2x
(b) y = ln(x
2
+ 2x + 1) (c) y =
Solution
(a) The function x
3
e
2x
involves the product of two simpler functions, x
3
and e
2x
, so we need to use the pro-
duct rule to differentiate it. Putting
u = x
3
and v = e
2x
gives
= 3x
2
and = 2e
2x
By the product rule
= u + v
= x
3
[2e
2x
] + e
2x
[3x
2
]
= 2x
3
e
2x
+ 3x
2
e
2x
There is a common factor of x
2
e
2x
, which goes into the first term 2x times and into the second term
3 times. Hence
= x
2
e
2x
(2x + 3)
(b) The expression ln(x
2
+ 2x + 1) can be regarded as a function of a function, so we can use the chain rule
to differentiate it. We first differentiate the outer log function to get
and then multiply by the derivative of the inner function, x
2
+ 2x + 1, which is 2x + 2. Hence
=
2x + 2
x
2
+ 2x + 1
dy
dx
1
x
2
+ 2x + 1
dy
dx
du
dx
dv
dx
dy
dx
dv
dx
du
dx
e
3x
x
2
+ 2
MFE_C04h.qxd 16/12/2005 11:19 Page 335